Quality of life of college students: The effects of state anxiety and academic stress with self-control as a mediator - Nuriyyatiningrum, Nadya Ariyani Hasanah; Zikrinawati, Khairani; Lestari, Puji; Madita, Rach (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
College education is expected to equip students with various types of knowledge. In reality, however, the learning process is not always easy. Problems can occur and affect students' quality of life. This study aims to examine the effect of state anxiety and academic stress on the quality of life through the mediation of student self-control. A quantitative method was used involving a sample of 400 students from 24 provinces in Indonesia. The measuring instruments employed were the World Health Organization Quality of Life (WHOQOL), The State Anxiety Scale, the Academic Stress Scale, and the Brief Self-Control Scale. Path analysis was conducted using R software. It was found that self-control partially mediates the effect of state anxiety on the quality of life. State anxiety has a direct effect, with a standardized coefficient of -.351 (p < .01), and an indirect one, with a standardized coefficient of -.150 (p < .01) on reducing the quality of life through the mediation of self-control. Academic stress has no indirect effect on the quality of life through the mediation of self-control with a standardized coefficient of -.000 (p = .990, p > .05). However, it was found to play a direct role in reducing the quality of life, with a standardized coefficient of -.207 (p < .01). The findings indicate the multi-dynamic impacts of state anxiety and academic stress toward the quality of life of students. Therefore, the development of anxiety and stress-management skills in students need to be addressed in the higher education management system in order to maintain the quality of life of students.